Fostering Interaction with Cultural Heritage Material via Annotations: The FAST-CAT Way - CONLAN, OWEN; HAMPSON, CORMAC (Springer, Berlin Heidelberg, 2013)
This paper describes the innovative annotation facilities of the CULTURA portal for digital humanties, which are aimed at improving the interaction of non specialist users and general public with cultural heritage contents. The annotation facilities are comprised by two modules: the FAST annotation service as back-end and the CAT Web front-end integrated in the CULTURA portal.
Bridging between Cultural Heritage Institutions
Proceedings of the 9th Italian Research Conference on Digital Libraries (IRCDL 2013)
PUBLISHED
Keywords: CULTURA; Digital Humanities; Intelligent Content & Communications